2009
DOI: 10.1159/000199715
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Acute Inflammatory and Chronic Structural Asthma-Like Responses between C57BL/6 and BALB/c Mice

Abstract: Background: The interactions between airway responsiveness, structural remodelling and inflammation in allergic asthma remain poorly understood. Prolonged challenge with inhaled allergen is necessary to replicate many of the features of airway wall remodelling in mice. In both mice and humans, genetic differences can have a profound influence on allergy, inflammation, airway responsiveness and structural changes. Methods: The aim of this study was to provide a comparative analysis of allergen-induced airway ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
45
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 82 publications
(80 reference statements)
12
45
1
1
Order By: Relevance
“…We used the immunodominant allergen from the Dermatophagoides pteronyssinus species of house dust mite (HDM), Der p 1, a relevant human allergen. As expected based on previous studies (8,11), C57BL/6J mice exhibited a stronger inflammatory response than did BALB/cJ mice, yet showed a striking decrease in airway responsiveness to methacholine. Using gene expression analysis, we identified a set of down-regulated G-protein-coupled receptors (GPCRs) involved in airway smooth muscle contraction that may mediate this response.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…We used the immunodominant allergen from the Dermatophagoides pteronyssinus species of house dust mite (HDM), Der p 1, a relevant human allergen. As expected based on previous studies (8,11), C57BL/6J mice exhibited a stronger inflammatory response than did BALB/cJ mice, yet showed a striking decrease in airway responsiveness to methacholine. Using gene expression analysis, we identified a set of down-regulated G-protein-coupled receptors (GPCRs) involved in airway smooth muscle contraction that may mediate this response.…”
supporting
confidence: 89%
“…For example, the two most commonly used inbred strains, C57BL/6J and BALB/cJ, differ in ovalbumin models of allergic disease (10,11). Furthermore, the link between allergic inflammation and AHR is also strain-dependent and model-dependent, with certain strains manifesting either or both phenotypes as a function of the induction of different allergen-response pathways (e.g., IL-4/ CD4 1 T-cell-dependent pathways (12) versus IL-5/eosinophildependent pathways (13)), and of the route or timing of exposure (9).…”
mentioning
confidence: 99%
“…In this context, OVA-challenged Mmp9-deficient mice displayed lower eosinophilia and hyperresponsiveness (9), whereas other authors using a different experimental protocol (far higher doses of allergen) reported increased eosinophilia in Mmp9 KO mice (13). The importance of the experimental protocol used to assess a phenotype in mice is further highlighted by various reports stating that there are important differences when considering various strains of mice (32,33). Notably, the present study provides evidence for similar exacerbated eosinophilia and increased AHR in Adamts12 2/2 mice of similar background, sensitized and challenged with two different allergens, the "classical" OVA and the very significant and widespread allergen for human asthmatics, HDM.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we performed our experiments using OVA in C57BL/6 mice who have been shown to be less responsive to metacholine compared with other mouse strains such as BALB/c (38,39). It was further suggested that the genetic background of mice influences several aspects of the acute allergic phenotype, including airway hyperresponsiveness (38,39).…”
Section: Discussionmentioning
confidence: 97%